Integrated networks of dental services. The Cuban case - Pedro López Puig (Editorial Ciencias Médicas, 2015)
Introduction: Cuba has a unique way of organizing health services within them; dental services are perhaps one of the most exquisite pieces of the broad array of benefits to which the Cuban population has access. In the Latin American context there is no reference of a public dental care system with universal coverage, which has developed a set of integrated and comprehensive benefits such as Cuba. From these statements, the following questions arise: Does the Cuban network of dental services with the attributes of integration proposed by international organizations? What time is network integration? What are the challenges for the future? Development: the practical challenge of achieving the objectives of the National Program of Comprehensive Care for the Population Stomatology has an integrated health service delivery. Its reserves of improvement system can be identified as a set of attributes related to: integration linking with basic equipment health clinic; the participation of the family, community and intersectoral management of health problems, among others. The Cuban model integrates all the functions inherent to health systems: service delivery, stewardship and management, financing, and coordination. Conclusions: Cuban network of dental services incorporated in its design and implementation attributes of integration proposed by the Pan American Health Organization. No scientifically supported information is available on the level of integration the Cuban network of dental services reaches, nor the impact of the phenomena of integration/fragmentation of the services provided. It poses as a challenge for the future, to conduct a research that demonstrates the impact of the phenomena of integration/fragmentation in stomatology services network.